The effects of climate change on the phenology of corn in the RDD-Toluca - Granados Ramírez Rebeca; Sarabia Rodríguez Asael Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
The most likely climate change is a rise of 2 °C in average air temperature; with respect to rainfall the projected change is greater, in some cases a 40% decrease; however, it is to be expected that there regions where precipitation increases. These changes will affect certain periods of the life of cultivated plants, a situation that will affect productivity. The aim of this work is to analyze the possible disturbances that can be brought about by climate change in corn production in the Rural Development District of Toluca in the State of Mexico, Mexico. The results obtained with the Hadley Climate model from the emission scenarios A2 and B2 (horizon 2050) show that the temperature and precipitation variables will have negative effects in the phenological development of corn, mainly affecting flowering, which could significantly decrease production.